IndPropInductively Defined Propositions
Inductively Defined Propositions
In past chapters, we have seen two ways of stating that a number n is even: We can say
- Rule ev_0: The number 0 is even.
- Rule ev_SS: If n is even, then S (S n) is even.
Such definitions are often presented using inference rules, they consist of a line separating the premises above from the conclusion below:
(ev_0) | |
even 0 |
even n | (ev_SS) |
even (S (S n)) |
-------- (ev_0)
even 0
-------- (ev_SS)
even 2
-------- (ev_SS)
even 4
even 0
-------- (ev_SS)
even 2
-------- (ev_SS)
even 4
Inductive Definition of Evenness
Inductive even : nat → Prop :=
| ev_0 : even 0
| ev_SS (n : nat) (H : even n) : even (S (S n)).
| ev_0 : even 0
| ev_SS (n : nat) (H : even n) : even (S (S n)).
We can think of the definition of even as defining a Coq
property even : nat → Prop, together with primitive theorems
ev_0 : even 0 and ev_SS : ∀ n, even n → even (S (S n)).
That definition can also be written as follows...
Inductive even : nat → Prop :=
| ev_0 : even 0
| ev_SS : ∀n, even n → even (S (S n)).
| ev_0 : even 0
| ev_SS : ∀n, even n → even (S (S n)).
Such "constructor theorems" have the same status as proven theorems. In particular, we can use Coq's apply tactic with the rule names to prove even for particular numbers...
Theorem ev_4 : even 4.
Proof. apply ev_SS. apply ev_SS. apply ev_0. Qed.
Proof. apply ev_SS. apply ev_SS. apply ev_0. Qed.
... or we can use function application syntax:
Theorem ev_4' : even 4.
Proof. apply (ev_SS 2 (ev_SS 0 ev_0)). Qed.
Proof. apply (ev_SS 2 (ev_SS 0 ev_0)). Qed.
We can also prove theorems that have hypotheses involving even.
Theorem ev_plus4 : ∀n, even n → even (4 + n).
Proof.
intros n. simpl. intros Hn.
apply ev_SS. apply ev_SS. apply Hn.
Qed.
Proof.
intros n. simpl. intros Hn.
apply ev_SS. apply ev_SS. apply Hn.
Qed.
Using Evidence in Proofs
In other words, if someone gives us evidence E for the assertion even n, then we know that E must have one of two shapes:
- E is ev_0 (and n is O), or
- E is ev_SS n' E' (and n is S (S n'), where E' is evidence for even n').
Inversion on Evidence
Theorem ev_inversion :
∀(n : nat), even n →
(n = 0) ∨ (∃n', n = S (S n') ∧ even n').
Proof.
intros n E.
destruct E as [ | n' E'].
- (* E = ev_0 : even 0 *)
left. reflexivity.
- (* E = ev_SS n' E' : even (S (S n')) *)
right. ∃n'. split. reflexivity. apply E'.
Qed.
∀(n : nat), even n →
(n = 0) ∨ (∃n', n = S (S n') ∧ even n').
Proof.
intros n E.
destruct E as [ | n' E'].
- (* E = ev_0 : even 0 *)
left. reflexivity.
- (* E = ev_SS n' E' : even (S (S n')) *)
right. ∃n'. split. reflexivity. apply E'.
Qed.
Which tactics are needed to prove this goal?
(1) destruct
(2) discriminate
(3) destruct, discriminate
(4) These tactics are not sufficient to solve the goal.
n : nat
E : even n
F : n = 1
======================
true = false
E : even n
F : n = 1
======================
true = false
Theorem ev_minus2 : ∀n,
even n → even (pred (pred n)).
Proof.
intros n E.
destruct E as [| n' E'].
- (* E = ev_0 *) simpl. apply ev_0.
- (* E = ev_SS n' E' *) simpl. apply E'.
Qed.
even n → even (pred (pred n)).
Proof.
intros n E.
destruct E as [| n' E'].
- (* E = ev_0 *) simpl. apply ev_0.
- (* E = ev_SS n' E' *) simpl. apply E'.
Qed.
However, this variation cannot easily be handled with destruct.
Theorem evSS_ev : ∀n,
even (S (S n)) → even n.
Proof.
intros n E.
destruct E as [| n' E'].
- (* E = ev_0. *)
(* We must prove that n is even from no assumptions! *)
Abort.
even (S (S n)) → even n.
Proof.
intros n E.
destruct E as [| n' E'].
- (* E = ev_0. *)
(* We must prove that n is even from no assumptions! *)
Abort.
Theorem evSS_ev : ∀n, even (S (S n)) → even n.
Proof. intros n H. apply ev_inversion in H. destruct H.
- discriminate H.
- destruct H as [n' [Hnm Hev]]. injection Hnm.
intro Heq. rewrite Heq. apply Hev.
Qed.
Proof. intros n H. apply ev_inversion in H. destruct H.
- discriminate H.
- destruct H as [n' [Hnm Hev]]. injection Hnm.
intro Heq. rewrite Heq. apply Hev.
Qed.
Coq provides a tactic called inversion, which does the work of
our inversion lemma and more besides.
Theorem evSS_ev' : ∀n,
even (S (S n)) → even n.
Proof.
intros n E.
inversion E as [| n' E'].
(* We are in the E = ev_SS n' E' case now. *)
apply E'.
Qed.
even (S (S n)) → even n.
Proof.
intros n E.
inversion E as [| n' E'].
(* We are in the E = ev_SS n' E' case now. *)
apply E'.
Qed.
Theorem one_not_even : ¬even 1.
Proof.
intros H. apply ev_inversion in H.
destruct H as [ | [m [Hm _]]].
- discriminate H.
- discriminate Hm.
Qed.
Theorem one_not_even' : ¬even 1.
intros H. inversion H. Qed.
Proof.
intros H. apply ev_inversion in H.
destruct H as [ | [m [Hm _]]].
- discriminate H.
- discriminate Hm.
Qed.
Theorem one_not_even' : ¬even 1.
intros H. inversion H. Qed.
Theorem inversion_ex1 : ∀(n m o : nat),
[n; m] = [o; o] →
[n] = [m].
Proof.
intros n m o H. inversion H. reflexivity. Qed.
Theorem inversion_ex2 : ∀(n : nat),
S n = O →
2 + 2 = 5.
Proof.
intros n contra. inversion contra. Qed.
[n; m] = [o; o] →
[n] = [m].
Proof.
intros n m o H. inversion H. reflexivity. Qed.
Theorem inversion_ex2 : ∀(n : nat),
S n = O →
2 + 2 = 5.
Proof.
intros n contra. inversion contra. Qed.
The tactic inversion actually works on any H : P where P is defined by Inductive:
- For each constructor of P, make a subgoal and replace H by how exactly this constructor could have been used to prove P.
- Discard contradictory subgoals (such as ev_0 above).
- Generate auxiliary equalities (as with ev_SS above).
Which tactics are needed to prove this goal,
in addition to simpl and apply?
(1) inversion
(2) inversion, discriminate
(3) inversion, rewrite plus_comm
(4) inversion, rewrite plus_comm, discriminate
(5) These tactics are not sufficient to prove the goal.
n : nat
E : even (n + 2)
=====================
even n
E : even (n + 2)
=====================
even n
Lemma ev_even_firsttry : ∀n,
even n → ∃k, n = double k.
Proof.
(* WORK IN CLASS *) Admitted.
even n → ∃k, n = double k.
Proof.
(* WORK IN CLASS *) Admitted.
Lemma ev_even : ∀n,
even n → ∃k, n = double k.
Proof.
intros n E.
induction E as [|n' E' IH].
- (* E = ev_0 *)
∃0. reflexivity.
- (* E = ev_SS n' E'
with IH : exists k', n' = double k' *)
destruct IH as [k' Hk'].
rewrite Hk'. ∃(S k'). reflexivity.
Qed.
even n → ∃k, n = double k.
Proof.
intros n E.
induction E as [|n' E' IH].
- (* E = ev_0 *)
∃0. reflexivity.
- (* E = ev_SS n' E'
with IH : exists k', n' = double k' *)
destruct IH as [k' Hk'].
rewrite Hk'. ∃(S k'). reflexivity.
Qed.
As we will see in later chapters, induction on evidence is a
recurring technique across many areas, and in particular when
formalizing the semantics of programming languages, where many
properties of interest are defined inductively.
Inductive Relations
One useful example is the "less than or equal to" relation on
numbers.
Inductive le : nat → nat → Prop :=
| le_n n : le n n
| le_S n m (H : le n m) : le n (S m).
Notation "m ≤ n" := (le m n).
| le_n n : le n n
| le_S n m (H : le n m) : le n (S m).
Notation "m ≤ n" := (le m n).
Theorem test_le1 :
3 ≤ 3.
Proof.
(* WORK IN CLASS *) Admitted.
Theorem test_le2 :
3 ≤ 6.
Proof.
(* WORK IN CLASS *) Admitted.
Theorem test_le3 :
(2 ≤ 1) → 2 + 2 = 5.
Proof.
(* WORK IN CLASS *) Admitted.
3 ≤ 3.
Proof.
(* WORK IN CLASS *) Admitted.
Theorem test_le2 :
3 ≤ 6.
Proof.
(* WORK IN CLASS *) Admitted.
Theorem test_le3 :
(2 ≤ 1) → 2 + 2 = 5.
Proof.
(* WORK IN CLASS *) Admitted.
Definition lt (n m:nat) := le (S n) m.
Notation "m < n" := (lt m n).
Notation "m < n" := (lt m n).
Here are a few more simple relations on numbers:
Inductive square_of : nat → nat → Prop :=
| sq n : square_of n (n * n).
Inductive next_nat : nat → nat → Prop :=
| nn n : next_nat n (S n).
| sq n : square_of n (n * n).
Inductive next_nat : nat → nat → Prop :=
| nn n : next_nat n (S n).
Define next_even : nat → nat → Prop such that next_even a b holds
iff b is the first even natural number that is greater than a.
Inductive next_even : nat → nat → Prop :=
| ne_1 n : even (S n) → next_even n (S n)
| ne_2 n (H : even (S (S n))) : next_even n (S (S n)).
Case Study: Regular Expressions
Inductive reg_exp {T : Type} : Type :=
| EmptySet
| EmptyStr
| Char (t : T)
| App (r1 r2 : reg_exp)
| Union (r1 r2 : reg_exp)
| Star (r : reg_exp).
| EmptySet
| EmptyStr
| Char (t : T)
| App (r1 r2 : reg_exp)
| Union (r1 r2 : reg_exp)
| Star (r : reg_exp).
We connect regular expressions and strings via the following rules, which define when a regular expression matches some string:
- The expression EmptySet does not match any string.
- The expression EmptyStr matches the empty string [].
- The expression Char x matches the one-character string [x].
- If re1 matches s1, and re2 matches s2,
then App re1 re2 matches s1 ++ s2.
- If at least one of re1 and re2 matches s,
then Union re1 re2 matches s.
- Finally, if we can write some string s as the concatenation
of a sequence of strings s = s_1 ++ ... ++ s_k, and the
expression re matches each one of the strings s_i,
then Star re matches s.
We can easily translate this informal definition into an Inductive one as follows:
Inductive exp_match {T} : list T → reg_exp → Prop :=
| MEmpty : exp_match [] EmptyStr
| MChar x : exp_match [x] (Char x)
| MApp s1 re1 s2 re2
(H1 : exp_match s1 re1)
(H2 : exp_match s2 re2) :
exp_match (s1 ++ s2) (App re1 re2)
| MUnionL s1 re1 re2
(H1 : exp_match s1 re1) :
exp_match s1 (Union re1 re2)
| MUnionR re1 s2 re2
(H2 : exp_match s2 re2) :
exp_match s2 (Union re1 re2)
| MStar0 re : exp_match [] (Star re)
| MStarApp s1 s2 re
(H1 : exp_match s1 re)
(H2 : exp_match s2 (Star re)) :
exp_match (s1 ++ s2) (Star re).
| MEmpty : exp_match [] EmptyStr
| MChar x : exp_match [x] (Char x)
| MApp s1 re1 s2 re2
(H1 : exp_match s1 re1)
(H2 : exp_match s2 re2) :
exp_match (s1 ++ s2) (App re1 re2)
| MUnionL s1 re1 re2
(H1 : exp_match s1 re1) :
exp_match s1 (Union re1 re2)
| MUnionR re1 s2 re2
(H2 : exp_match s2 re2) :
exp_match s2 (Union re1 re2)
| MStar0 re : exp_match [] (Star re)
| MStarApp s1 s2 re
(H1 : exp_match s1 re)
(H2 : exp_match s2 (Star re)) :
exp_match (s1 ++ s2) (Star re).
Notice that this clause in our informal definition...
... is not explicitly reflected in the above definition. Do we
need to add something?
(1) Yes, we should add a rule for this.
(2) No, one of the other rules already covers this case.
(3) No, the lack of a rule actually gives us the behavior we
want.
- The expression EmptySet does not match any string.
Again, for readability, we can also display this definition using inference-rule notation. At the same time, let's introduce a more readable infix notation.
Notation "s =~ re" := (exp_match s re) (at level 80).
(MEmpty) | |
[] =~ EmptyStr |
(MChar) | |
[x] =~ Char x |
s1 =~ re1 s2 =~ re2 | (MApp) |
s1 ++ s2 =~ App re1 re2 |
s1 =~ re1 | (MUnionL) |
s1 =~ Union re1 re2 |
s2 =~ re2 | (MUnionR) |
s2 =~ Union re1 re2 |
(MStar0) | |
[] =~ Star re |
s1 =~ re s2 =~ Star re | (MStarApp) |
s1 ++ s2 =~ Star re |
Example reg_exp_ex1 : [1] =~ Char 1.
Example reg_exp_ex2 : [1; 2] =~ App (Char 1) (Char 2).
Example reg_exp_ex3 : ¬([1; 2] =~ Char 1).
Proof.
apply MChar.
Qed.
apply MChar.
Qed.
Example reg_exp_ex2 : [1; 2] =~ App (Char 1) (Char 2).
Proof.
apply (MApp [1] _ [2]).
- apply MChar.
- apply MChar.
Qed.
apply (MApp [1] _ [2]).
- apply MChar.
- apply MChar.
Qed.
Example reg_exp_ex3 : ¬([1; 2] =~ Char 1).
Proof.
intros H. inversion H.
Qed.
intros H. inversion H.
Qed.
We can define helper functions for writing down regular expressions. The reg_exp_of_list function constructs a regular expression that matches exactly the list that it receives as an argument:
Fixpoint reg_exp_of_list {T} (l : list T) :=
match l with
| [] ⇒ EmptyStr
| x :: l' ⇒ App (Char x) (reg_exp_of_list l')
end.
Example reg_exp_ex4 : [1; 2; 3] =~ reg_exp_of_list [1; 2; 3].
match l with
| [] ⇒ EmptyStr
| x :: l' ⇒ App (Char x) (reg_exp_of_list l')
end.
Example reg_exp_ex4 : [1; 2; 3] =~ reg_exp_of_list [1; 2; 3].
Proof.
simpl. apply (MApp [1]).
{ apply MChar. }
apply (MApp [2]).
{ apply MChar. }
apply (MApp [3]).
{ apply MChar. }
apply MEmpty.
Qed.
simpl. apply (MApp [1]).
{ apply MChar. }
apply (MApp [2]).
{ apply MChar. }
apply (MApp [3]).
{ apply MChar. }
apply MEmpty.
Qed.
Lemma MStar1 :
∀T s (re : @reg_exp T) ,
s =~ re →
s =~ Star re.
(* WORK IN CLASS *) Admitted.
∀T s (re : @reg_exp T) ,
s =~ re →
s =~ Star re.
(* WORK IN CLASS *) Admitted.
Naturally, proofs about exp_match often require induction.
Fixpoint re_chars {T} (re : reg_exp) : list T :=
match re with
| EmptySet ⇒ []
| EmptyStr ⇒ []
| Char x ⇒ [x]
| App re1 re2 ⇒ re_chars re1 ++ re_chars re2
| Union re1 re2 ⇒ re_chars re1 ++ re_chars re2
| Star re ⇒ re_chars re
end.
match re with
| EmptySet ⇒ []
| EmptyStr ⇒ []
| Char x ⇒ [x]
| App re1 re2 ⇒ re_chars re1 ++ re_chars re2
| Union re1 re2 ⇒ re_chars re1 ++ re_chars re2
| Star re ⇒ re_chars re
end.
Theorem in_re_match : ∀T (s : list T) (re : reg_exp) (x : T),
s =~ re →
In x s →
In x (re_chars re).
Proof.
intros T s re x Hmatch Hin.
induction Hmatch
as [| x'
| s1 re1 s2 re2 Hmatch1 IH1 Hmatch2 IH2
| s1 re1 re2 Hmatch IH | re1 s2 re2 Hmatch IH
| re | s1 s2 re Hmatch1 IH1 Hmatch2 IH2].
(* WORK IN CLASS *) Admitted.
The remember Tactic
Lemma star_app: ∀T (s1 s2 : list T) (re : @reg_exp T),
s1 =~ Star re →
s2 =~ Star re →
s1 ++ s2 =~ Star re.
Proof.
intros T s1 s2 re H1.
s1 =~ Star re →
s2 =~ Star re →
s1 ++ s2 =~ Star re.
Proof.
intros T s1 s2 re H1.
A naive first attempt at setting up the induction. (Note
that we are performing induction on evidence!)
induction H1
as [|x'|s1 re1 s2' re2 Hmatch1 IH1 Hmatch2 IH2
|s1 re1 re2 Hmatch IH|re1 s2' re2 Hmatch IH
|re''|s1 s2' re'' Hmatch1 IH1 Hmatch2 IH2].
as [|x'|s1 re1 s2' re2 Hmatch1 IH1 Hmatch2 IH2
|s1 re1 re2 Hmatch IH|re1 s2' re2 Hmatch IH
|re''|s1 s2' re'' Hmatch1 IH1 Hmatch2 IH2].
We can get through the first case...
- (* MEmpty *)
simpl. intros H. apply H.
simpl. intros H. apply H.
... but most cases get stuck. For MChar, for instance, we
must show that
s2 =~ Char x' → x' :: s2 =~ Char x',
which is clearly impossible.
- (* MChar. Stuck... *)
Abort.
Abort.
The problem is that induction over a Prop hypothesis only works properly with hypotheses that are completely general, i.e., ones in which all the arguments are variables, as opposed to more complex expressions, such as Star re.
Lemma star_app: ∀T (s1 s2 : list T) (re re' : reg_exp),
re' = Star re →
s1 =~ re' →
s2 =~ Star re →
s1 ++ s2 =~ Star re.
re' = Star re →
s1 =~ re' →
s2 =~ Star re →
s1 ++ s2 =~ Star re.
This works, but it requires making the statement of the lemma
a bit ugly, which is a shame. Fortunately, there is a better way:
Abort.
The tactic remember e as x causes Coq to (1) replace all occurrences of the expression e by the variable x, and (2) add an equation x = e to the context. Here's how we can use it to show the above result:
Lemma star_app: ∀T (s1 s2 : list T) (re : reg_exp),
s1 =~ Star re →
s2 =~ Star re →
s1 ++ s2 =~ Star re.
Proof.
intros T s1 s2 re H1.
remember (Star re) as re'.
s1 =~ Star re →
s2 =~ Star re →
s1 ++ s2 =~ Star re.
Proof.
intros T s1 s2 re H1.
remember (Star re) as re'.
We now have Heqre' : re' = Star re.
generalize dependent s2.
induction H1
as [|x'|s1 re1 s2' re2 Hmatch1 IH1 Hmatch2 IH2
|s1 re1 re2 Hmatch IH|re1 s2' re2 Hmatch IH
|re''|s1 s2' re'' Hmatch1 IH1 Hmatch2 IH2].
induction H1
as [|x'|s1 re1 s2' re2 Hmatch1 IH1 Hmatch2 IH2
|s1 re1 re2 Hmatch IH|re1 s2' re2 Hmatch IH
|re''|s1 s2' re'' Hmatch1 IH1 Hmatch2 IH2].
The Heqre' is contradictory in most cases, allowing us to
conclude immediately.
- (* MEmpty *) discriminate.
- (* MChar *) discriminate.
- (* MApp *) discriminate.
- (* MUnionL *) discriminate.
- (* MUnionR *) discriminate.
- (* MChar *) discriminate.
- (* MApp *) discriminate.
- (* MUnionL *) discriminate.
- (* MUnionR *) discriminate.
The interesting cases are those that correspond to Star. Note
that the induction hypothesis IH2 on the MStarApp case
mentions an additional premise Star re'' = Star re, which
results from the equality generated by remember.
- (* MStar0 *)
injection Heqre'. intros Heqre'' s H. apply H.
- (* MStarApp *)
injection Heqre'. intros H0.
intros s2 H1. rewrite <- app_assoc.
apply MStarApp.
+ apply Hmatch1.
+ apply IH2.
* rewrite H0. reflexivity.
* apply H1.
Qed.
injection Heqre'. intros Heqre'' s H. apply H.
- (* MStarApp *)
injection Heqre'. intros H0.
intros s2 H1. rewrite <- app_assoc.
apply MStarApp.
+ apply Hmatch1.
+ apply IH2.
* rewrite H0. reflexivity.
* apply H1.
Qed.
Case Study: Improving Reflection
Theorem filter_not_empty_In : ∀n l,
filter (fun x ⇒ n =? x) l ≠ [] →
In n l.
Proof.
intros n l. induction l as [|m l' IHl'].
- (* l = *)
simpl. intros H. apply H. reflexivity.
- (* l = m :: l' *)
simpl. destruct (n =? m) eqn:H.
+ (* n =? m = true *)
intros _. rewrite eqb_eq in H. rewrite H.
left. reflexivity.
+ (* n =? m = false *)
intros H'. right. apply IHl'. apply H'.
Qed.
filter (fun x ⇒ n =? x) l ≠ [] →
In n l.
Proof.
intros n l. induction l as [|m l' IHl'].
- (* l = *)
simpl. intros H. apply H. reflexivity.
- (* l = m :: l' *)
simpl. destruct (n =? m) eqn:H.
+ (* n =? m = true *)
intros _. rewrite eqb_eq in H. rewrite H.
left. reflexivity.
+ (* n =? m = false *)
intros H'. right. apply IHl'. apply H'.
Qed.
The first subcase (where n =? m = true) is a bit awkward.
It would be annoying to have to do this kind of thing all the
time.
We can streamline this by defining an inductive proposition that yields a better case-analysis principle for n =? m. Instead of generating an equation such as (n =? m) = true, which is generally not directly useful, this principle gives us right away the assumption we really need: n = m.
Inductive reflect (P : Prop) : bool → Prop :=
| ReflectT (H : P) : reflect P true
| ReflectF (H : ¬P) : reflect P false.
| ReflectT (H : P) : reflect P true
| ReflectF (H : ¬P) : reflect P false.
The only way to produce evidence for reflect P true is by
showing P and using the ReflectT constructor.
If we invert this reasoning, it says we can extract evidence for
P from evidence for reflect P true.
Theorem iff_reflect : ∀P b, (P ↔ b = true) → reflect P b.
Proof.
(* WORK IN CLASS *) Admitted.
Proof.
(* WORK IN CLASS *) Admitted.
(The right-to-left implication is left as an exercise.)
The advantage of reflect over the normal "if and only if" connective is that, by destructing a hypothesis or lemma of the form reflect P b, we can perform case analysis on b while at the same time generating appropriate hypothesis in the two branches (P in the first subgoal and ¬ P in the second).
To use reflect to produce a better proof of filter_not_empty_In, we begin by recasting the eqb_iff_true lemma in terms of reflect:
Lemma eqbP : ∀n m, reflect (n = m) (n =? m).
Proof.
intros n m. apply iff_reflect. rewrite eqb_eq. reflexivity.
Qed.
Proof.
intros n m. apply iff_reflect. rewrite eqb_eq. reflexivity.
Qed.
A smoother proof of filter_not_empty_In now goes as follows. Notice how the calls to destruct and apply are combined into a single call to destruct.
Theorem filter_not_empty_In' : ∀n l,
filter (fun x ⇒ n =? x) l ≠ [] →
In n l.
Proof.
intros n l. induction l as [|m l' IHl'].
- (* l = *)
simpl. intros H. apply H. reflexivity.
- (* l = m :: l' *)
simpl. destruct (eqbP n m) as [H | H].
+ (* n = m *)
intros _. rewrite H. left. reflexivity.
+ (* n <> m *)
intros H'. right. apply IHl'. apply H'.
Qed.
filter (fun x ⇒ n =? x) l ≠ [] →
In n l.
Proof.
intros n l. induction l as [|m l' IHl'].
- (* l = *)
simpl. intros H. apply H. reflexivity.
- (* l = m :: l' *)
simpl. destruct (eqbP n m) as [H | H].
+ (* n = m *)
intros _. rewrite H. left. reflexivity.
+ (* n <> m *)
intros H'. right. apply IHl'. apply H'.
Qed.